1979
DOI: 10.2307/3180377
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Management Strategies for Agricultural Producers

Abstract: LA and uncertainty are pervasive phenomena in production agriculture. Many factors, including weather events, diseases, insect infestations, general economic conditions, the development and adoption of technological innovations, and public and private institutional policies.,interact to create a unique decision making environment for the agricultural producer. General economic conditions in the economy, particularly the inflation rate, have increased prices paid by farm operators for operating inputs and capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Early research on the subject utilized mathematical programming with a focus on examining whole farm planning in the presence of risky alternatives, and under conditions of uncertainty (e.g. Fruend, 1956;Hazell 1971;Mapp et al 1979). In an effort to examine systematic (i.e., risk correlated among producers) and non-diversifiable risk, later studies, for example, implemented the use of the coefficient of variation of total indemnities paid by crop insurers in addition to a selection of parametric and non-parametric methods to estimate probability functions of crop yields, which in turn, tend to have implications on the income generating capacity and profits of farm businesses (e.g., Miranda, and Glauber.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research on the subject utilized mathematical programming with a focus on examining whole farm planning in the presence of risky alternatives, and under conditions of uncertainty (e.g. Fruend, 1956;Hazell 1971;Mapp et al 1979). In an effort to examine systematic (i.e., risk correlated among producers) and non-diversifiable risk, later studies, for example, implemented the use of the coefficient of variation of total indemnities paid by crop insurers in addition to a selection of parametric and non-parametric methods to estimate probability functions of crop yields, which in turn, tend to have implications on the income generating capacity and profits of farm businesses (e.g., Miranda, and Glauber.…”
Section: Previous Researchmentioning
confidence: 99%
“…While risk consideration has been extensively examined in production agriculture (e.g., Mapp et al 1979;Just and Pope 1979;Antle 1983;Harwood et al 1999;Meuwissen, van Asseldonk, and Huirne 2008;Ullah et al 2016), exploring the relationship between risk management per se and economic performance is apt to contribute yet another perspective to the continually growing body of risk-related literature. To mitigate the risk associated with farm production, many farmers rely primarily on their participation in off-farm work and/or in farm programs.…”
Section: Introductionmentioning
confidence: 99%
“…Hazell and Scandizzo [21] and Paris [33] are some examples of a large number of studies which developed several variants of risk programming models. Several empirical investigations have also been made using these models in selecting optimal crop mix and in testing the behaviourial assumptions of the producers towards risk [10,16,18,24,25,28,32,37]. Binswanger [8,9] using an experimental gambling approach to study the attitude towards risk of semi-arid tropical farmers of India concluded that wealth does not influence risk significantly at higher pay-off levels and that differences in investment behaviour could not be explained by the differences in their constraint sets.…”
Section: The Modelmentioning
confidence: 99%
“…Wolgin (1975) stated that traditional tests of economic efficiency in agriculture are generally mis-specified when farmers make decisions under risk. Since risk plays an important role both in the use of inputs and production of outputs, some of the previous studies have focused on risk in the production process (Just 1974;Aigner et al 1977;Just & Pope 1978;Mapp et al 1979;Chambers 1983;Kumbhakar 1987;Battese & Coelli 1995;Battese et al 1997). thus, this framework extends and includes producers' risk preferences into empirical analysis by Love & Buccola (1991), Kumbhakar (1993), Saha et al (1994), Chavas & holt (1996), Isik & Khanna (2002), Settlage & Preckel (2002), Shaik & helmers (2003).…”
Section: Introductionmentioning
confidence: 99%